The polymorphism analysis and therapy vaccine target epitopes screening of HPV-35 E6 E7 among the threaten α-9 HPV in Sichuan area - He, Jiaoyu; Li, Tianjun; Cheng, Chunlan; Li, Ning; Gao, Peng; Lei, Dan; Liang, Rong; Ding, Xianping (Virology journal, 2024)
High-risk human papilloma virus (HR-HPV) persistent infection is closely associated with the development of cervical cancer and squamous intraepithelial lesion (SIL).The α-9 HPVs, which is predominantly composed of HR-HPV types, account for 75% of HR-HPV infection in Sichuan. The oncoproteins E6 and E7 of HPV play a crucial role in tumor initiation and progression. Notably, HPV-35 is the only HR-HPV type within the α-9 genus that is not included in the nine-valent HPV prophylactic vaccine. Cervical cell samples obtained from Sichuan were collected for HPV detection and genotyping. Among the 406 HPV-positive samples, 31 HPV-35 were detected, 24 HPV-35 E6 and 26 E7 were successfully amplified and sequenced, five nucleotide mutations in E6 and three in E7 were detected, T232C, T434G of E6 (W78R, I145R) and C67T, G84T of E7 (H23Y, L28F) were non-synonymy mutation. PAML 4.8 server was used to detect positive selection sites of HPV-35 E6, E7, and E6 is W78R. Phyre2 were used to predict and analyze protein structures, W78R made influences on protein structure. IEDB were used to screen epitopes vaccine target for HPV-35 affection therapy, and 5 HPV-35 E6 and 3 HPV-35 E7 most potential epitopes were obtained, the most potential peptides for therapy vaccine design were 79-91YRYSVYGETLEKQ, 45-60FACYDLCIVREGQPY, 124-135RFHNIGGRWTGR of E6; 3-19GEITTLQDYVLDLEPEA, 38-47TIDGPAGQAK, 70-88VQSTHIDIRKLEDLLMGTF of E7 and W78R mainly decreased the epitopes affinity. Conclusions Amino acid substitution in the positive selection sites of HPV-35 E6 and E7 genes have been found to influence protein structure and to decrease the overall affinity of antigen epitopes. This observation aligns with the evolutionary significance of positive selection site, which may confer advantages to the virus by making infected cells more challenging for the immune system to detect, thereby enhancing HPV’s adaptability to the host environment. The polymorphism analysis of HPV-35 E6, E7 contributes to the enrichment of α-9 HPV data in Sichuan China, which is instrumental in improving the effectiveness of clinical detection. Furthermore, these findings provide a relevant theoretical foundation for the prevention and treatment of HPV-related diseases.